Tecnologias sociais de convivência com o semiárido: um estudo de caso no rio grande do norte – brasil - Silva, Camilo Vinícius Trindade (Universidade Federal Rural do Semi-Árido, 2018)
The social technologies of living with the Brazilian semiarid emerge as a viable alternative, in opposition to the model of policy to combat the drought that, for decades, was adopted by the public power. However, it is necessary to analyze the design of this new approach from the perspective of beneficiaries and agents of Technical Assistance and Rural Extension. In this way, the objective was to understand the perception of farmers and agents of Technical Assistance and Rural Extension of Rio Grande do Norte (RN) about the potentialities, functionalities and appropriation of the Social Technologies of coexistence with the semi-arid. The study was carried out in the State of Rio Grande do Norte, in rural communities of 45 municipalities. It was promoted the collection of data and information on the social technologies of coexistence with the semiarid implanted in the municipalities inserted in this territory, through the experience reports produced by agents / scholarship holders of rural extension. The reports were standardized and in a semi-structured questionnaire format, with open and closed questions. Data analysis was divided into two stages: the first consisted in identifying the productive activities carried out by the families and the verification of the social technologies implanted in them. The second one was related to the perception of the family farmers and the agents Technical Assistance and Rural Extension regarding the effectiveness of the social technologies of living with the semi-arid region and the importance of the technical assistance and rural extension in this context. Excel 2016 was used to process the data in order to perform the basic descriptive statistics. For the qualitative method, a detailed reading of the collected material and the excerpts from the experiences of the scholarship recipients and the perception of these and the farmers was carried out, using Content Analysis. The social technologies of living with the semi-arid region have proved to be efficient in the perception of the scholars who work in Technical Assistance and Rural Extension, even in the face of the water scarcity evidenced in the territory of Potiguar. Technical assistance and rural extension are of fundamental importance for the diffusion of social technologies and for the promotion of sustainable rural development. The social technologies of living with the semi-arid are important for the families inserted in the rural communities of the State, since it reflects in the improvement of the quality of life, considering the social, economic and environmental aspects involved in the context of those
Keywords: Barragem subterrânea; Segurança hídrica; Soberania alimentar; Percepção; Recursos hídricos; Underground dam; Water security; Food sovereignty; Perception; Water resources; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO